On the evidence for electron-electron scattering in the electrical resistivity In. - Bressan, Oscar José; Ridner, A. E.; Luengo, C. A.; Alascio, Blas Rafael (1970)
Fil: Bressan, O. J. Comisión Nacional de Energía Atómica; Argentina